2020
DOI: 10.1002/adsc.202001460
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Chemistry with Lewis Acidity‐Diminished B(aam) and B(dan) Groups: Borylation Reactions and Direct Cross‐Couplings

Abstract: This review describes recent advances in the synthesis of anthranilamide/1,8‐diaminonaphthalene‐substituted organoboron compounds with diminished boron Lewis acidity via catalytic B(aam)‐ and B(dan)‐installing borylation reactions, which have attracted growing attention especially in the last five years owing to their unique reactivity, regioselectivity, and the outstanding stability toward air and moisture of organoboron compounds obtained therefrom. Direct Suzuki–Miyaura cross‐couplings with R–B(aam)/B(dan),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 69 publications
0
22
0
Order By: Relevance
“…In the present context, however, one has to keep in mind that the use of −B(aam) derivatives for Suzuki‐Miyaura cross coupling reactions is uncommon. Yet, a recent investigation provides encouraging precedent in that it showed that aryl‐B(aam) derivatives allow for direct cross coupling without need for prior unmasking of the corresponding boronic acid [35,41] . The results compiled in Scheme 4 do not only confirm this result: it is actually stunning to find that the Suzuki‐Miyaura reaction outcompetes a Stille cross coupling under the chosen conditions; [54] in the basic aqueous medium, protodestannylation did not interfere.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the present context, however, one has to keep in mind that the use of −B(aam) derivatives for Suzuki‐Miyaura cross coupling reactions is uncommon. Yet, a recent investigation provides encouraging precedent in that it showed that aryl‐B(aam) derivatives allow for direct cross coupling without need for prior unmasking of the corresponding boronic acid [35,41] . The results compiled in Scheme 4 do not only confirm this result: it is actually stunning to find that the Suzuki‐Miyaura reaction outcompetes a Stille cross coupling under the chosen conditions; [54] in the basic aqueous medium, protodestannylation did not interfere.…”
Section: Resultsmentioning
confidence: 99%
“…Yet, a recent investigation provides encouraging precedent in that it showed that aryl-B(aam) derivatives allow for direct cross coupling without need for prior unmasking of the corresponding boronic acid. [35,41] The results compiled in Scheme 4 do not only confirm this result: it is actually stunning to find that the Suzuki-Miyaura reaction outcompetes a Stille cross coupling under the chosen conditions; [54] in the basic aqueous medium, protodestannylation did not interfere. This somewhat unusual yet gratifying "inverse" order of reactivity brings functionalized alkenylstannanes into reach in isomerically pure form which would be difficult to prepare otherwise.…”
Section: Boron-selective Cross Couplingmentioning
confidence: 99%
See 1 more Smart Citation
“…Organoboron compounds 1 play a pivotal role in synthetic organic chemistry, where they have enabled a myriad of useful transformations 2–4 and have also been used in the field of materials science. 5 The most advantageous application of organoboron compounds was achieved in medicinal chemistry 6 where several boron-containing drugs reached the market in the last two decades.…”
Section: Introductionmentioning
confidence: 99%
“…[3,4] In this context, we have been involved in developing new borylation and stannylation reactions; in the case of the borylation, our attention has particularly been directed toward diminishing the inherent Lewis acidity of boron moieties to be installed by employing naphthalene-1,8-diaminato (dan) or anthranilamidato (aam) as a substituent on boron centers. [5] In view of the boron Lewis acidity, which strongly impacts reactivity and regio/stereoselectivity in borylation reactions, we envisaged that the use of B(dan)-or B(aam)-based reagents with diminished boron-Lewis acidity could bring about a drastic change in behavior in the borylation reactions, and properties of organoboranes obtained therefrom. On the other hand, since organotrialkylstannanes, used mainly as stannylating reagents in this study, basically exhibit little Lewis acidity, we have been interested in increasing the tin-Lewis acidity by electron-withdrawing inductive effect of organic groups on tin center, thus leading to unique reactivities and stannylation reactions therewith.…”
Section: Introductionmentioning
confidence: 99%